The case of Inditex and ASOS : mergers and acquisitions - Krüper, Dominik Marcel (2015)
The apparel and fashion retailing business is currently in transition from brick and mortar to online. The fast fashion giants Inditex and H&M face competition from fashion e-commerce, while struggling themselves with their online rollout. Simultaneously, the stars of online-only fast fashion retailing, like ASOS and Zalando, experience aggressive competition that causes pricing pressure and shrinking margins. In contrast to ASOS’s market capitalizations over one year ago, with price-earnings ratios above 100, the stand-alone valuation indicates that ASOS is currently trading close to fair value, which makes it an attractive takeover target. Acquiring ASOS would enable Inditex to efficiently enter e-commerce with a famous online-only brand. ASOS shareholders could exit their investment, leaving the company with a strategic investor to enable further expansion. The strategic fit allows for synergies to increase the valuation of the combined firm. Selling Inditex products on the ASOS marketplace and extending ASOS’s deliver-to store option with the Inditex store network would increase sales. Cost synergies are expected from the consolidation of sourcing and manufacturing as well as the rationalization of administrative and organizational redundancies. Overall, synergies of approximately €12bn would add shareholder value of approximately 11,47% to Inditex’s current market cap. ASOS shareholders will be offered €66,75 or 2,25 Inditex shares per ASOS share, respectively 30% premium on fair value. The mix of cash and stock enables Inditex to utilize its cash pile, avoid leverage and align interests.